The Mandarin Club : a novel - Warburg, Gerald Felix (2006)
Could the U.S. be losing sight of other international threats as we busy ourselves with the war on terror and the Axis of Evil? That's the underlying premise in this complex political thriller. The lives of a brainy group of Stanford friends--all well schooled in various aspects of Chinese culture, language, and politics--intersect 25 years after graduation as China becomes not only a land of opportunity for U.S. exports but also a growing threat to national security.
Keywords: Espionage, Chinese -- Fiction; Quakers -- Fiction; Diplomatic relations; Espionage, Chinese; Politics and government; Quakers